VIRTUAL REALITY IN RARE CRITICAL EVENT TRAINING: A SYSTEMATIC REVIEW OF EFFICACY IN ENHANCING READINESS AND STRESS MANAGEMENT - Jacek Borawski; Julia Burdon-Sajnóg; Zofia Szymona-Kuciewicz; Klaudia Katarzyna Bartela; Julia Katarzyna Dusiel; Anna Wałachowska; Alicja Tabian; Paulina Kozłowska; Jakub Smęt; Aleksandra Beata Chojnacka (International Journal of Innovative Technologies in Social Science, 2026)
Training for Rare Critical Events (RCEs)-high-stakes, low-frequency occurrences across specialized fields such as critical care and emergency services-presents formidable educational challenges. Ethical and safety constraints severely limit the opportunity for real-world exposure, leading to significant performance deterioration and high cognitive load when an RCE occurs. Virtual Reality (VR) technology is emerging as an impactful and scalable training solution capable of delivering high-fidelity experiential learning. This systematic review aims to synthesize current evidence on the efficacy of VR-based training in RCE preparation, specifically examining its dual impact on operational readiness in technical and non-technical skills and the development of effective stress management and cognitive coping mechanisms. The review of studies reveals that VR environments designed with high psychological fidelity, significantly enhance procedural adherence, decision-making speed, and non-technical skills during simulated RCEs. Crucially, the literature demonstrates VR’s unique capability to safely implement stress inoculation training. Studies comparing pre- and post-VR training show a measurable reduction in physiological stress markers, such as decreased mean heart rate and improved heart rate variability (HRV), along with lower self-reported anxiety during subsequent high-pressure tests. This suggests superior transfer of training for stress management compared to traditional simulation. The evidence supports VR as a potent, justifiable, and cost-effective tool for RCE preparedness, offering unparalleled opportunity for repeated practice under authentic, high-stress conditions. Future efforts must focus on standardizing VR metrics and conducting robust longitudinal studies to confirm the long-term retention of these critical skills.